Eye of horus – Erratum revealed a prescription survey - Jijin, M. J.; Jaishankar, H. P.; Krupashankar, R.; Veena, S. N.; Kavitha, A. P.; Shobha, R. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The aim of this study was to survey the quality and the content of prescription of practitioners and also assess the legibility of alphabet, and short form of the drug. Methods: A survey of all prescription received by the patients that were written by general practitioners, consulting physicians and dentists in and around Virajpet and Madikeri (south Coorg) was included.The prescriptions were photocopied and returned back to the patients. The prescription was scored and analyzed by a qualified medical investigator. Results: A total of 171 prescription samples were collected. In most prescriptions, one or more aspects of patient’s personal details were missing. Concerned doctor’s details also lacked in most cases. 40.3% of the prescriptions were obtained wherein short form of the drug was used for prescribing drug. Legibility of alphabet was also evaluated and the most confusing letter noted in our study was letter “C”; followed by A, T, S, O, G, and D in this study the letter Rx was written in 7% of the prescription and in 19% prescription it was replaced by word “Adv” and 74% of prescription without symbol of Rx. Conclusions: The present data shows most prescriptions in the study was inadequate and important details were lacking, legibility of prescription was poor in rating.